Menganalisis Rantai Nilai untuk Meningkatkan Keunggulan Kompetitif Bisnis Energi Panas Bumi - Bahri Lubis, Syaiful (PT Bone Jaya Kreatif, 2023)
PT Sorik Marapi Geothermal Power is a geothermal energy company, value chain analysis is one of the tools that is needed by all companies to achieve the competitive advantage especially in geothermal development. The implementation of a value chain is as strategies how a company will be able to know all the activities of business to achieve competitive advantage and produce sustainable products. PT Sorik Marapi Geothermal Power applies the best technology & innovation to develop geothermal energy with more cost-efficiency. This research used qualitative research with case study by doing observation & interview in the field. The result of this research was supported by the primary data from informant & secondary data from literature review & the previous research. The achievement of competitive advantage in developing geothermal energy with value chain by applying binary cycle power plant system, drilling effectively, and knock-down construction system. The competitive advantage should be supported by the right manpower have the significant role to achieve on company’s target. PT Sorik Marapi Geothermal Power could achieve the competitive advantage by having the efficient cost strategy because company could produce energy 1 unit/year & already generated with 140MW capacity of energy to PT PLN trough 150 KV transmission line. In process business of PT Sorik Marapi Geothermal gets the profit 2.2 energy compared with conventional technology & has the agreement of electricity energy is cheaper than BPP of Sumatera section with the price 8.1 cent.